2020
DOI: 10.1007/s42087-020-00139-1
|View full text |Cite
|
Sign up to set email alerts
|

Combatting Against Covid-19 & Misinformation: A Systematic Review

Abstract: Accompanied by false information, mass media content is hindering efforts to cope with the current outbreak. Although the World Health Organization and other concerned bodies are notified regarding misinformation, myths and rumors are highly prevalent. This paper aims to highlight the misinformation and its potential impacts during the Covid-19 by using the Systematic Review Approach. The researcher randomly selected n = 35 research articles published from 2015 to 2020, witnessing the misinformation as a major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 39 publications
(39 reference statements)
0
46
0
1
Order By: Relevance
“…COVID-19 is the first new media infodemic. This infodemic also contains a large amount of misinformation, leading to adverse consequences (Ali 2020) The systematic review, n= 35 peer-reviewed research articles Social media contains both information and misinformation. When users receive any information, they share it without further authentication (Al-Zaman 2020)…”
Section: Misinformation and New Mediamentioning
confidence: 99%
See 3 more Smart Citations
“…COVID-19 is the first new media infodemic. This infodemic also contains a large amount of misinformation, leading to adverse consequences (Ali 2020) The systematic review, n= 35 peer-reviewed research articles Social media contains both information and misinformation. When users receive any information, they share it without further authentication (Al-Zaman 2020)…”
Section: Misinformation and New Mediamentioning
confidence: 99%
“…The impacts of misinformation can be further estimated from a recent incident in Nigeria when health practitioners found hundreds of cases of an overdose of hydroxychloroquine as they were told it could develop immunity against COVID-19 (McLaughlin 2020). Figure 2 gives a brief idea of the current research study, classifying misinformation and describing their harmful impacts (Ali 2020).…”
Section: Misinformation and New Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, we found that some misconceptions related to COVID-19 spread, treatment and prevention remain persistent to varying degrees among the participants. Evidence from similar epidemics (such as Middle East respiratory syndrome (MERS) and Swine flu (H1N1) 23,24 ) show that misconceptions, myths and rumours always exist in the general population during and following an outbreak, and this is also true for the COVID-19 pandemic 22,25 .…”
Section: Discussionmentioning
confidence: 99%